Cry of silence [videorecording (DVD)] - Crozier, Robin E.; Aukai, Felipe; Daysh, Charlot; Monaco, Jim (Film director) (Deskpop Entertainment, 2026)
Newlyweds' bliss shatters when Maggie disappears in a town haunted by a serial killer. As Frank's frantic search unravels dark truths about her past, Maggie must find her last strength to outwit her captor in a desperate fight for freedom.